Refractive and topographic corneal changes associated with increased inflammatory mediators in tears after COVID-19 - Reviglio, Victor Eduardo (2024)
This is a rare case report of a sudden shift to myopic astigmatism and topography alterations in a patient who experienced mild coronavirus disease 2019 (COVID‑19) symptoms. A complete ophthalmologic evaluation, slit‑lamp examination, corneal topography, and tear sampling for biochemical analysis were performed. Elevated corneal K‑values were found, indicating abnormal anterior corneal curvature, based on the asymmetric corneal steepening index (cone location and magnitude index) in a Galilei G6 study. Tear analysis demonstrated elevated levels of interleukin (IL)‑1β, IL‑6, IP‑10, IL‑8, interferon‑β, and prometalloproteinase‑9. Ophthalmologists should maintain a high level of suspicion when symptoms suggestive of corneal involvement arise in patients recently infected with severe acute respiratory syndrome coronavirus 2.